Vertical gradients of neutral winds observed by ICON and estimated by the Horizontal Wind Model during the geomagnetic storm on August 26−28, 2021 - JiaWei Wu; Chao Xiong; YuYang Huang; YunLiang Zhou (Earth and Planetary Physics)
The Michelson Interferometer for Global High-resolution Thermospheric Imaging (MIGHTI) onboard the Ionospheric Connection Explorer (ICON) satellite offers the opportunity to investigate the altitude profile of thermospheric winds. In this study, we used the red-line measurements of MIGHTI to compare with the results estimated by Horizontal Wind Model 14 (HWM14). The data selected included both the geomagnetic quiet period (December 2019 to August 2022) and the geomagnetic storm on August 26–28, 2021. During the geomagnetic quiet period, the estimations of neutral winds from HWM14 showed relatively good agreement with the observations from ICON. According to the ICON observations, near the equator, zonal winds reverse from westward to eastward at around 06:00 local time (LT) at higher altitudes, and the stronger westward winds appear at later LTs at lower altitudes. At around 16:00 LT, eastward winds at 300 km reverse to westward, and vertical gradients of zonal winds similar to those at sunrise hours can be observed. In the middle latitudes, zonal winds reverse about 2–4 h earlier. Meridional winds vary more significantly than zonal winds with seasonal and latitudinal variations. According to the ICON observations, in the northern low latitudes, vertical reversals of meridional winds are found at 08:00–13:00 LT from 300 to 160 km and at around 18:00 LT from 300 to 200 km during the June solstice. Similar reversals of meridional winds are found at 04:00–07:00 LT from 300 to 160 km and at 22:00–02:00 LT from 270 to 200 km during the December solstice. In the southern low latitudes, meridional wind reversals occur at 08:00–11:00 LT from 200 to 160 km and at 21:00–02:00 LT from 300 to 200 km during the June solstice. During the December solstice, reversals of the meridional wind appear at 20:00–01:00 LT below 200 km and at 06:00–11:00 LT from 300 to 160 km. In the northern middle latitudes, the northward winds are dominant at 08:00–14:00 LT at 230 km during the June solstice. Northward winds persist until 16:00 LT at 160 and 300 km. During the December solstice, the northward winds are dominant from 06:00 to 21:00 LT. The vertical variations in neutral winds during the geomagnetic storm on August 26–28 were analyzed in detail. Both meridional and zonal winds during the active geomagnetic period observed by ICON show distinguishable vertical shear structures at different stages of the storm. On the dayside, during the main phase, the peak velocities of westward winds extend from a higher altitude to a lower altitude, whereas during the recovery phase, the peak velocities of the westward winds extend from lower altitudes to higher altitudes. The velocities of the southward winds are stronger at lower altitudes during the storm. These vertical structures of horizontal winds during the storm could not be reproduced by the HWM14 wind estimations, and the overall response to the storm of the horizontal winds in the low and middle latitudes is underestimated by HWM14. The ICON observations provide a good dataset for improving the HWM wind estimations in the middle and upper atmosphere, especially the vertical variations.